Bronsmedaljen i ett tvåmannalopp. En kvalitativ textanalys av tredjepartiers misslyckande i federala val i USA sedan 76:e kongressen (1939-1940) - Stoméus,Samuel; Salberg,Emil (2023)
Abstract This qualitative literature study discusses the political system in the United States with regard to third parties eligibility on a federal level and third option presidential candidates and why they have had difficulties organizing and succeeding in the congressional and presidential elections since the 76th Congress (1939-1940). We analyze this matter alongside the frameworking Duverger's law, contrasting it to the micromega-rule and rational choice theory to further try to understand how complex the third party situation is in the US besides Duverger-esque explanations. The capitalistic sparkle is discussed and how presidential financing through campaign funds as such hurts third party candidates that are challenging Democratic and Republican candidates. Further, the two-party system benefits from manipulative redistricting, ballot access laws and incumbency advantage in the electoral process, further marginalizing third parties. These obstacles may be too much for third parties to overcome if current circumstances stay the same with regard to federal elections.
Keywords: tredjepartier; tvåpartisystem; Duvergers lag; Micromega-regeln; Rational Choice Theory